The Trinitarian Dimension of the Life of the Baptised - Klich, Anna (Studia Warmińskie, 2024)
The subject of this theological and exegetical study is the Trinitarian dimension of the baptised in the pericope Rom 8:14-17, as read in the light of other Old and New Testament texts and of the witness of the living tradition of the Church. The aim of this article is to examine what are the essential dimensions of the life of the baptised indicated by St. Paul in the Letter to the Romans (8:14-17), and how, in a mystical way, he shows the action of the Holy Spirit in the baptised person. The first stage of the exegetical analysis determines the literary context of the pericope, allowing it to indicate the essential specificity of a Christian, that is, the acceptance of the Holy Spirit as a guide in their way of life. The Holy Spirit makes known the gift of adoption bringing the believer into a relationship with God the Father that is similar to that between the Father and the Son. The dignity of God’s children is bound up in their inheritance of eternal life. The second part of this article explains the dimension of cooperation between the Christian and God and the relationship between conscious co-suffering with Christ and sharing in God’s glory with him. Finally, it must be emphasised that God, who gives his Holy Spirit to his children and wants to be intimate with them, is active in the process of becoming like Christ. On the part of humankind, cooperation is needed. This consists primarily of attentive listening to the Holy Spirit and of conscious union with Christ, especially in the tribulations of everyday life. This process leads to becoming with Christ co-heirs to eternal glory.